Epigenetics in the Eye: An Overview of the Most Relevant Ocular Diseases - Alkozi, Hanan A.; Franco, Rafael; Pintor, Jesús J. (Frontiers in Genetics, 2017)
Sight for mammals is one of the most appreciated senses. In humans there are several factors that contribute to the increment in all kind of diseases. This mini-review will focus on some eye diseases whose prevalence is steadily increasing year after year for non-genetic reasons, namely cataracts, dry eye and glaucoma. Ageing, diet, inflammation, drugs, oxidative stress, seasonal and circadian style-of-live changes are impacting on disease prevalence by epigenetics factors, defined as stable heritable traits that is not explained by changes in DNA sequence. The mini-review will concisely show the data showing epigenetics marks in these diseases and on how knowledge on the epigenetic alterations may guide therapeutic approaches to keep a healthy eye.